2019
DOI: 10.1016/j.jconrel.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy sensitization of glioblastoma by focused ultrasound-mediated delivery of therapeutic liposomes

Abstract: In glioblastoma, the benefit from temozolomide chemotherapy is largely limited to a subgroup of patients (30-35%) with tumors exhibiting methylation of the promoter region of the O 6-methylguanine-DNA methyltransferase (MGMT) gene. In order to allow more patients to benefit from this treatment, we explored magnetic resonance image-guided microbubble-enhanced low-intensity pulsed focused ultrasound (LIFU) to transiently open the blood-brain barrier and deliver a first-in-class liposome-loaded small molecule MGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 50 publications
0
52
0
Order By: Relevance
“…The limited brain delivery and penetration was addressed employing MRIg-FUS, which has been shown to enhance the deposition of different drugs in various organs [56][57][58] while being well tolerated by animals [59][60][61][62][63] and humans. [64,65] Moreover, MRIg-FUS showed therapeutic efficacy per se on phosphorylated Tau and amyloid plaques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited brain delivery and penetration was addressed employing MRIg-FUS, which has been shown to enhance the deposition of different drugs in various organs [56][57][58] while being well tolerated by animals [59][60][61][62][63] and humans. [64,65] Moreover, MRIg-FUS showed therapeutic efficacy per se on phosphorylated Tau and amyloid plaques.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were i.v. injected with 2.4 mL kg −1 of microbubbles (600 µL min −1 injection speed) 30 s before the beginning of the FUS sequence, which lasted for 3 min with fixed parameters during the whole session (length: 10 ms pulse; sequence: 1 Hz pulse repetition frequency; acoustic pressure emitted: 0.9 MPa; estimated pressure in situ: 0.4-0.5 MPa; duty cycle: 1%; mechanical index: 0.7; expected thermal index: ≈0) and was adapted from a protocol described by Papachristodoulou et al [58] Twenty min after FUS sequence, rats were i.v. injected with 75 µL per animal of gadolinium-DOTA (Guerbet, Paris, France) and T1-weighted MR images were acquired to confirm BBB opening.…”
Section: Methodsmentioning
confidence: 99%
“…The limited brain delivery and penetration was addressed employing MRIg-FUS, which has been shown to enhance the deposition of different drugs in various organs [57][58][59] while being well tolerated by animals [60][61][62][63] and humans [64,65]. Moreover, MRIg-FUS showed therapeutic efficacy per se on phosphorylated Tau and amyloid plaques [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…The rats were i.v. injected with 2.4 mL kg -1 of microbubbles (600 µL/min injection speed) 30 s before the beginning of the FUS sequence, which lasted for 3 min (Length: 5-10 ms pulse; Sequence: 1 Hz pulse repetition frequency; Pressure in situ: 0.4-0.5 mPa) and was adapted from a protocol described by Papachristodoulou et al [59]. Twenty min after FUS sequence, rats were i.v.…”
Section: Magnetic Resonance Imaging-guided Low Intensity-pulsed Focusmentioning
confidence: 99%
“…The dose-limiting toxicity of O 6 -BTG was myelosuppression (78). Papachristodoulou et al reported that a liposomal O 6 BTG can efficiently target MGMT, thereby sensitizing murine and human glioma cells to TMZ in vitro and magnetic resonance image-guided microbubbleenhanced low-intensity pulsed focused ultrasound mediates the delivery of the stable liposomal MGMT inactivator into the tumor region resulting in complete MGMT depletion in vivo (79).…”
Section: Targeting Mgmt Proteinmentioning
confidence: 99%